Exceptionally low daily energy expenditure in the bamboo-eating giant panda - Nie, Yonggang; Speakman, John R.; Wu, Qi; Zhang, Chenglin; Hu, Yibo; Xia, Maohua; Yan, Li; Hambly, Catherine; Wang, Lu; Wei, Wei; Zhang, Jinguo; Wei, Fuwen (Science (American Association for the Advancement of Science), 2015)
The carnivoran giant panda has a specialized bamboo diet, to which its alimentary tract is poorly adapted. Measurements of daily energy expenditure across five captive and three wild pandas averaged 5.2 megajoules (MJ)/day, only 37.7% of the predicted value (13.8 MJ/day). For the wild pandas, the mean was 6.2 MJ/day, or 45% of the mammalian expectation. Pandas achieve this exceptionally low expenditure in part by reduced sizes of several vital organs and low physical activity. In addition, circulating levels of thyroid hormones thyroxine (T4) and triiodothyronine (T3) averaged 46.9 and 64%, respectively, of the levels expected for a eutherian mammal of comparable size. A giant panda–unique mutation in the DUOX2 gene, critical for thyroid hormone synthesis, might explain these low thyroid hormone levels. A combination of morphological, behavioral, physiological, and genetic adaptations, leading to low energy expenditure, likely enables giant pandas to survive on a bamboo diet.